Tissue‐engineered tendon constructs for rotator cuff repair in sheep. Issue 1 (31st July 2017) - Novakova, Stoyna S.; Mahalingam, Vasudevan D.; Florida, Shelby E.; Mendias, Christopher L.; Allen, Answorth; Arruda, Ellen M.; Bedi, Asheesh; Larkin, Lisa M.
ABSTRACT: Current rotator cuff repair commonly involves the use of single or double row suture techniques, and despite successful outcomes, failure rates continue to range from 20 to 95%. Failure to regenerate native biomechanical properties at the enthesis is thought to contribute to failure rates. Thus, the need for technologies that improve structural healing of the enthesis after rotator cuff repair is imperative. To address this issue, our lab has previously demonstrated enthesis regeneration using a tissue‐engineered graft approach in a sheep anterior cruciate ligament (ACL) repair model. We hypothesized that our tissue‐engineered graft designed for ACL repair also will be effective in rotator cuff repair. The goal of this study was to test the efficacy of our Engineered Tissue Graft for Rotator Cuff (ETG‐RC) in a rotator cuff tear model in sheep and compare this novel graft technology to the commonly used double row suture repair technique. Following a 6‐month recovery, the grafted and contralateral shoulders were removed, imaged using X‐ray, and tested biomechanically. Additionally, the infraspinatus muscle, myotendinous junction, enthesis, and humeral head were preserved for histological analysis of muscle, tendon, and enthesis structure. Our results showed that our ETC‐RCs reached 31% of the native tendon tangent modulus, which was a modest, non‐significant, 11% increase over that of the suture‐only repairs. However, the histological analysis showed the regeneration of a native‐like enthesis in the ETG‐RC‐repaired animals. This advanced structural healing may improve over longer times and may diminish recurrence rates of rotator cuff tears and lead to better clinical outcomes. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:289–299, 2018.